N,N-Diethylurea-Catalyzed Amidation between Electron-Defficient Aryl Azides and Phenylacetaldehydes - Xie, Sheng (Org Lett, 2015)
[Image: see text] Urea structures, of which N,N-diethylurea (DEU) proved to be the most efficient, were discovered to catalyze amidation reactions between electron-defficient aryl azides and phenylacetaldehydes. Experimental data support 1,3-dipolar cycloaddition between DEU-activated enols and electrophilic phenyl azides, especially perfluoroaryl azides, followed by rearrangement of the triazoline intermediate. The activation of the aldehyde under near-neutral conditions was of special importance in inhibiting dehydration/aromatization of the triazoline intermediate, thus promoting the rearrangement to form aryl amides.